QBER Estimation in QKD Systems With Polarization Encoding - Muga, Nelson (2012)
A model for quantum BER estimation in polarization encoded quantum key distribution systems is presented. Both TDM and WDM based polarization control schemes are analyzed. It is shown that TDM presents some important advantages when compared with the WDM control scheme. In WDM, the polarization decorrelation between the reference and data signals is an intrinsic and very limitative impairment. This effect has a contribution to quantum BER that increases with the propagation distance, and is highly dependent on the fiber polarization mode dispersion. In the TDM control scheme, the polarization decorrelation is less critical and other issues, like the single photon detector and feedback polarization control system performance tend to dominate. We show that for long distances the fiber losses represent the main contribution to the total quantum BER. Nevertheless, for distances shorter than 70 km and frequencies higher than 5 MHz the after pulse detections provide an important contribution to the total quantum BER.